COMMUNICATION STRATEGY OF THE CENTRAL BUTTON DISTRICT TOURISM OFFICE ORGANIZATION IN DEVELOPING THE MUTIARA BEACH TOURISM DESTINATION, MAWASANGKA DISTRICT (Karya Ilmiah Mahasiswa (KIMA), 2024)
The research objectives of this study were (1) to determine the communication strategy of the tourism office of Central Buton Regency in developing the Mutiara Beach tourist destination, Mawasangka District. (2) To find out the form of development of the Mutiara Beach tourist destination, Mawasamgka District, Central Buton Regency. The type of research used is a qualitative description. The subjects in this study were the tourism office, tourist site officers, visitors or tourists. The research lasted for one month and was located in Central Buton District, Mawasangka District. The results showed that there were still many disturbances to the tourist facilities of Mutiara Beach, Central Buton Regency, Mawasangka District, such as a lack of clean water, damaged access roads.